THE RELEVANCE OF CHARACTER EDUCATION IN AL-KHUDORI’S NURUL YAQIN TO NATIONAL EDUCATION GOALS - Lailatus Sholichah Al Kufiyyah; Umi Salamah; Marpuah (Institut Bahri Asyiq Galis Bangkalan, 2026)
Indonesia’s National Education System (Law No. 20 of 2003) mandates the formation of a generation that is faithful, pious, and noble in character; yet this goal remains challenged by persistent moral decline among students in the era of globalization. Amidst the ongoing moral crisis and global developments, the book Nurul Yaqin by Shaykh Al-Khudori presents character values honesty, patience, justice, compassion, and exemplary behavior derived from the prophetic biography of Muhammad (PBUH), and this study examines how these values align with and contribute to the realization of Indonesia’s national education goals. This study aims to address two key questions: (1) To explore the concept of character education from Shaykh Al-Khudori’s perspective in Nurul Yaqin; and (2) To analyze the relevance of this concept to the goals of national education. A qualitative approach is employed, utilizing library research and a descriptive- analytical method. The findings show that: Shaykh Al-Khudori’s concept of character education in Nurul Yaqin aligns with national education goals. The values of honesty, patience, justice, compassion, and role modeling presented in this book are consistent with the effort to develop individuals who are faithful, pious, noble in character, knowledgeable, competent, creative, independent, democratic, and responsible.